2022
DOI: 10.1140/epjc/s10052-022-10405-x
|View full text |Cite
|
Sign up to set email alerts
|

Multiplicity dependence of charged-particle jet production in pp collisions at $$\mathbf {\sqrt{s}}=\mathbf {13~TeV}$$

Abstract: The multiplicity dependence of jet production in pp collisions at the centre-of-mass energy of $$\sqrt{s} = 13\ {\mathrm {TeV}}$$ s = 13 TeV is studied for the first time. Jets are reconstructed from charged particles using the anti-$$k_\mathrm {T}$$ k T … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 107 publications
1
1
0
Order By: Relevance
“…Furthermore, it is observed that the changes of these distributions in different multiplicity classes with respect to the minimum bias case are independent of the jet resolution parameter R and have a weak p T dependence, except for the very low p T domain. This indicates that jet production changes with event activity, but the slope of the spectrum stays similar to the one measured in MB events [6].…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Furthermore, it is observed that the changes of these distributions in different multiplicity classes with respect to the minimum bias case are independent of the jet resolution parameter R and have a weak p T dependence, except for the very low p T domain. This indicates that jet production changes with event activity, but the slope of the spectrum stays similar to the one measured in MB events [6].…”
Section: Resultssupporting
confidence: 68%
“…The analysis procedure for the measurement of the multiplicity dependence of jet production in pp collisions at s = 13 TeV is described in detail in Ref. [6].…”
Section: Analysis Detailsmentioning
confidence: 99%